Potential Cost Avoidance of Adverse Drug Reactions Prevention in Outpatient Pharmacy Department Ramathibodi Hospital Thailand - Nia Kurnia Sholihat; Wasin Chimsawat (MPI (Media Pharmaceutica Indonesiana), 2017)
Pharmacists’ intervention in hospital setting is very beneficial both in patients’ clinical outcomeand economic aspect, in terms of cost avoidance due to adverse drug reactions. This study was conductedto calculate cost avoidance of adverse drug reactions (ADR) prevention in outpatient pharmacydepartment in Ramathibodi Hospital Thailand. A retrospective database review of hospital pharmacyinterventions preventing adverse drug reaction was conducted at second floor pharmacy unit, Somdech-PhraDebaratana Medical Center, Ramathibodi hospital between 1 July 2013 and 31 December 2013. Potentialcost avoidance of ADR was calculated using diagnosis-related groups (DRG’s) data. Results showedthat the detection of ADR was 0.239%. The most frequent ADR came from Penicillin group was accountedfor 32.4% of total case. The estimated cost avoidance generated during July-December 2013 was ThaiBaht (THB) 592,320 to THB 1,257,428 (USD 19,278 to USD 40,925, value 2013). It can be concludedthat hospital pharmacists positively impacted on economic benefit of patients by providing ADR detection.More complete data are needed to get a better results of a real cost avoidance of ADR prevention.